Exploratory landscape metrics for agricultural sustainability - Vaz, Eric (2014)
Socioeconomic growth and urban change have been an increasing concern for decision makers in recent decades. The monitoring, mapping, and analysis of agricultural land use change, especially in areas where urban change has been high, is crucial. The collision between traditional economic activities related to agriculture in tourist areas such as the Algarve and current demand for tourism infrastructures in urban regions is also leading to loss of economic activity. This article uses a combined geographical information system approach with CORINE land cover datasets to perform a Shannon’s diversity index quantifying changes in agricultural areas. The article then expands on the nature of the agricultural changes observed, and offers a multi-temporal assessment by means of landscape metrics in order to understand the shifting land use patterns for the Algarve in land use planning and regional economic equilibrium: a) forest regions become transformed into agricultural areas and agricultural areas become urban; b) areas that are initially agricultural become scattered residential regions created by economic investors; and c) agricultural land use changes have a cyclical nature in which—in the course of the economic recession—such dynamic effects brought about a decrease in tourism and focus on traditional sectors.